2002
DOI: 10.1002/uog.19
|View full text |Cite
|
Sign up to set email alerts
|

Nasal bone hypoplasia in trisomy 21 at 15–22 weeks' gestation

Abstract: K E Y W O R D S:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
159
1
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 10 publications
9
159
1
9
Order By: Relevance
“…The findings of this study in a low-risk population, namely that all five fetuses with trisomy 21 and 4 and suggest that nasal bone hypoplasia is likely to be the single most sensitive and specific secondtrimester marker of trisomy 21. In the study of Cicero et al 4 in women undergoing second-trimester amniocentesis, nasal bone hypoplasia was observed in 21/35 (62%) trisomy 21 fetuses for a false-positive rate of 1%.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The findings of this study in a low-risk population, namely that all five fetuses with trisomy 21 and 4 and suggest that nasal bone hypoplasia is likely to be the single most sensitive and specific secondtrimester marker of trisomy 21. In the study of Cicero et al 4 in women undergoing second-trimester amniocentesis, nasal bone hypoplasia was observed in 21/35 (62%) trisomy 21 fetuses for a false-positive rate of 1%.…”
Section: Discussionmentioning
confidence: 63%
“…In the study of Cicero et al 4 in women undergoing second-trimester amniocentesis, nasal bone hypoplasia was observed in 21/35 (62%) trisomy 21 fetuses for a false-positive rate of 1%. Larger studies need to be performed to establish the exact role of nasal bone hypoplasia in second-trimester screening for trisomy 21, however existing data indicate that examination of the nasal bone should be included in the routine mid-trimester sonographic assessment of the fetus.…”
Section: Discussionmentioning
confidence: 95%
“…First, the evaluation of the nasal bone with ultrasound gives estimates of prevalence rather than incidence. Prevalence refers to the proportion of people in the target population with a certain condition/characteristic at a single point in time while incidence measures the occurrence of new cases during a specified period of time 2 . Given the high rate of attrition (i.e.…”
Section: Absent Nasal Bone: Applying the Right Terminology And Interpmentioning
confidence: 99%
“…In a previous study, 26% of these cases were found to have nuchal edema, and thereby, it was concluded that some of these cases may have increased NT at 10 to 14 weeks of gestation. 23 For a case with increased NT, fetal movement and posture of the joints should be examined.…”
mentioning
confidence: 99%